Edible backyards: climate change and urban food insecurity in Africa - Nkrumah, Bright (BioMed Central, 2018)
Background: Food insecurity is continuously seen as a major problem in Africa, and as a challenge confronting millions of Africa’s urban population. Although some city residents produce their own food and, therefore, are food secured, others continuously fnd it difcult to access arable land in order to keep animals or cultivate crops. Climate change, in addition, seems to worsen the food insecurity situation of the region’s urban population, especially in the face of drought and fooding waters. To this end, this study recommends that urban agriculture (UA) is well positioned to mitigate the adverse efect of climate change and improve food security. Results: The study found that the current problem posed by climate change to Africa’s urban food security is expected to worsen. Many urban populations are at risk of becoming victims of climate change through severe food supply problems caused by foods, droughts and hailstorms that afect food production in the hinterlands. African urban population has a role to play in fnding appropriate solution to sustain food security, especially through UA. Conclusion: The study concludes that African governments should endeavour to create the necessary conducive environment to encourage urban residents to engage in animal husbandry and food production.
Keywords: Food security - Africa; Urban agriculture - Africa; Climate changes - Economic aspects - Africa